PENINGKATAN LITERASI MAKANAN TERKAIT INFORMASI NILAI GIZI PADA LABEL MAKANAN KEMASAN - Dwijayanti, Ira; Mutiarani, Anugrah Linda; Firdaus, Angelina Putri; Lestari, Eka Harum (Poltekkes Kemenkes Mataram, 2025)
Obesity among adolescents remains a major health issue in Indonesia. According to data from the 2018 Basic Health Research, 16.0% of adolescents aged 12-15 years and 13.5% of adolescents aged 16-18 years are overweight or obese. Low literacy in reading food labels and nutritional value information can influence the incidence of adolescent obesity. the aim of this activity is to increase teenagers' knowledge and attitudes towards reading food labels and understanding nutritional information on packaged foods, thereby potentially reducing the incidence of obesity in adolescents. The education activity involved 42 students who actively participated in the entire educational series. It was focus on providing participants with a comprehensive overview of food labels and nutritional information, as well as instructions on how to read and interpret nutritional value information on packaged foods. The topic was delivered through a 60-minute session using posters as the primary educational material. The effectiveness of the educational activity was measured using a pre-test and post-test questionnaire consisting of 5 closed-ended questions. The Wilcoxon statistical test indicated a significant difference between pre-test and post-test results, with a p-value of 0.004. The educational activity successfully enhanced the students' understanding of food labels and nutritional information. Future activities should focus on further improving students' skills in reading and applying this knowledge in their daily lives.